2014
DOI: 10.1016/j.pain.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Persistent post-surgical pain and experimental pain sensitivity in the Tromsø study: Comorbid pain matters

Abstract: In a large survey incorporating medical examination (N=12,981), information on chronic pain and surgery was collected, and sensitivity to different pain modalities was tested. Tolerance to the cold pressor test was analysed with survival statistics for 10,486 individuals, perceived cold pressor pain intensity was calculated for 10,367 individuals, heat pain threshold was assessed for 4,054 individuals, and pressure pain sensitivity for 4,689 individuals. Persistent post-surgical pain, defined by self-report, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 43 publications
5
39
3
Order By: Relevance
“…48 Secondary hyperalgesia due to enhanced central processing may not necessarily directly affect postoperative spontaneous pain ratings, but may play a role in the development of chronic postsurgical pain. 9,17,20,21,28 Other studies using an incision model have shown that pretraumatic lidocaine injection, applied before an incision on the forearm of healthy volunteers, suppressed spontaneous pain, flare, and primary hyperalgesia more effectively than posttraumatic injection. Inhibition of secondary hyperalgesia by pretraumatic block indicated induction by peripheral input.…”
Section: Introductionmentioning
confidence: 99%
“…48 Secondary hyperalgesia due to enhanced central processing may not necessarily directly affect postoperative spontaneous pain ratings, but may play a role in the development of chronic postsurgical pain. 9,17,20,21,28 Other studies using an incision model have shown that pretraumatic lidocaine injection, applied before an incision on the forearm of healthy volunteers, suppressed spontaneous pain, flare, and primary hyperalgesia more effectively than posttraumatic injection. Inhibition of secondary hyperalgesia by pretraumatic block indicated induction by peripheral input.…”
Section: Introductionmentioning
confidence: 99%
“…This probably reflects random differences between the two study populations. In a large epidemiologic study, cold pressor data were shown to be influenced by age, gender, chronic pain and hypertension 20,21. In addition, small differences in context and methods are known to influence pain scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Johansen and coworkers found co-morbid pain to be strongly associated with persistent pain in the surgical site (15).…”
Section: Discussionmentioning
confidence: 99%